RETRACTED: Characteristics of value orientations and attitudes to communication in codependent women of different ages as predictors of the development of sustainable behavior - Kolenova Anastasia; Kukulyar Anna (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001